ANALISIS PELANGGARAN KODE ETIK ADVOKAT HOTMAN PARIS TERHADAP JHONNY ANDREAN - Rabawati, Dwytias Witarti; Anrolan Hello, Grendi; Anastasia Wijono, Maria; Konstantinus Soo, Yakobus; Mario Pignateli Milo, Derryl Yosef; Biola Tukan, Christian Andryan; Oshinta Joni, Maria Hilary; Oscar Elu, Januario (Gapenas Publisher, 2024)
The